2019
DOI: 10.3390/molecules24234232
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of the Conversion of Mandelonitrile and 2-Phenylpropionitrile by a Large Set of Variants Generated from a Nitrilase Originating from Pseudomonas fluorescens EBC191

Abstract: The arylacetonitrilase from the bacterium Pseudomonas fluorescens EBC191 has been intensively studied as a model to understand the molecular basis for the substrate-, reaction-, and enantioselectivity of nitrilases. The nitrilase converts various aromatic and aliphatic nitriles to the corresponding acids and varying amounts of the corresponding amides. The enzyme has been analysed by site-specific mutagenesis and more than 50 different variants have been generated and analysed for the conversion of (R,S)-mande… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 45 publications
1
9
0
Order By: Relevance
“…Each commercial compound yielded a similar pair of doublets with chemical shift values in line with those of the biologically-formed product but with distinctly different coupling constants; 15.6 for the trans versus 12.4 for the cis species (data not shown). Accordingly, the higher value of 15.6 Hz for the bioconversion product gave reason to conclude that the trans isomer of the monoamide ( trans -3-cyanoacrylamide) was formed and is consistent with the conventional mechanism of nitrilase-catalyzed reactions in which small quantities of the amide intermediate can escape from the enzyme [ 1 , 2 , 36 ].
Fig.
…”
Section: Resultssupporting
confidence: 61%
See 1 more Smart Citation
“…Each commercial compound yielded a similar pair of doublets with chemical shift values in line with those of the biologically-formed product but with distinctly different coupling constants; 15.6 for the trans versus 12.4 for the cis species (data not shown). Accordingly, the higher value of 15.6 Hz for the bioconversion product gave reason to conclude that the trans isomer of the monoamide ( trans -3-cyanoacrylamide) was formed and is consistent with the conventional mechanism of nitrilase-catalyzed reactions in which small quantities of the amide intermediate can escape from the enzyme [ 1 , 2 , 36 ].
Fig.
…”
Section: Resultssupporting
confidence: 61%
“…The demonstrated broad specificity for relatively large nitrile molecules is consistent with this. Moreover, like Nit6803 and other nitrilases capable of attacking dinitriles [ [31] , [32] , [33] , [34] , [35] , [36] ], Nit11764 also is able to act on only one of the cyano groups, the monocarboxylate being formed identified by 1 HNMR as trans -3-cyanoacrylate ( Fig. 6 ).…”
Section: Discussionmentioning
confidence: 99%
“…The analysis of the mandelic acid formed by chiral HPLC demonstrated that in both systems almost exclusively (R)-mandelic acid was formed (ee > 95%). This clearly demonstrated that the ( R )-oxynitrilase and the nitrilase were active in the whole cell catalysts because it was previously shown that the nitrilase from P. fluorescens EBC191 converts mandelonitrile in the absence of an oxynitrilase activity only with much lower enantioselectivity to ( R )-mandelic acid (with an ee of about 30%) and additionally forms higher amounts of mandelic acid amide from racemic mandelonitrile (Kiziak et al 2007 ; Stolz et al 2019 ).…”
Section: Resultsmentioning
confidence: 63%
“…Furthermore, (substituted) mandelic acid amide(s) are building blocks of several antibiotics, fungicides, and antioxidatives (Cederbaum et al 2004 ; Cole 1969 ; Ley and Bertram 2001 ). Therefore, it was disappointing that all previously studied variants of the nitrilase from P. fluorescens EBC191 which formed significant amounts of mandelic acid amide only formed ( S )-mandelic acid amide with a rather low-degree of enantioselectivity (Stolz et al 2019 ). In contrast, the efficient synthesis of ( R )-mandelic acid amide shown in the present study by the system expressing the ( R )-specific oxynitrilase and the amide forming nitrilase variant, opens new perspectives for the enantioselective synthesis of ( R )-hydroxycarboxamides.…”
Section: Discussionmentioning
confidence: 99%
“…Although molecular modeling of nitrilases and the interactions between their subunits and substrates have been reported [ 15 , 16 , 17 , 18 ], details regarding the molecular determinants of the catalytic efficiency of arylacetonitrilase have never, to the best of our knowledge, been reported. An understanding of the role of amino acid residues at the active microenvironment site may guide future protein design efforts to exploit the ubiquitous and industrially useful enzymes such as nitrilases [ 19 ].…”
Section: Introductionmentioning
confidence: 99%